MOTIVASI INDONESIA MENANDATANGANI PREFERENTIAL TRADE AGREEMENT (PTA) DENGAN MESIR TAHUN 2011 - Indra Pratama; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study analyzes the factors that motivate Indonesia signed a preferential trade agreement with Mesir in 2011 . the reasons which prompted Indonesia to cooperate with Mesir to better cooperation , free trade agreements . This study will also explain the Indonesian trip begins negotiations of the Comprehensive Trade on Economic Partnership (CTEP) by Indonesia and Mesir signed in 2005 , both from the development and scope of negotiations .Keywords: Preferential Trade Agreement, Cooperation, Factors.